Cardiotoxicity of anthracyclines and cardioprotection. Facts and myths - Deptała, Andrzej; Omyła-Staszewska, Joanna; Staszewska-Skurczyńska, Marzanna (Contemporary Oncology/Współczesna Onkologia, 2004)
Irreversible cardiac toxicity often leads to death or permanent disability. Chemotherapy can cause heart damage. Anthracyclines, which belong to the most effective „broad spectrum” anticancer agents can induce cardiotoxicity. Distinct forms of myocardial injury occur quite frequently after the use of all clinically available anthracyclines, such as doxorubicin, daunorubicin, epirubicin, esorubicin, aclarubicin, idarubicin, and the anthracycline-derivative mitoxantrone. Several risk factors of anthracycline-induced cardiomyopathy have been identified during the last two decades; they are the following: total cumulative dose, age (over 65 or under 4 years), mediastinal radiotherapy >20 Gy prior to anthracycline-based chemotherapy (or concurrent), previous use of anthracycline-containing regimens, pre-existing cardiac disease (valvular, ischemic, myocardial), hypertension, diabetes, liver diseases, and parallel cyclophosphamide exposure. Regarding these observations, two questions arise, i.e. (1) what is the exact mechanism of the anthracycline-induced cardiotoxicity? (2) are there any proven methods eliminating the risk of developing such adverse effects? Despite intensive research work and many clinical observations, to date it is still difficult to answer precisely those questions. Besides, during the last 30 years numerous spectacular theories about anthracycline-induced cardiotoxicity have been created, thus plenty of chemical compounds have been promoted for cardioprotection. Following evidence-based medicine, we have been trying to pick up all the facts on anthracycline-induced cardiotoxicity and cardioprotection, and to contrast these facts with some myths that still exist in the medical environment.